Shariah board governance and sustainability performance: analysis of sharia banking in Indonesia - Puspitasari, Novia Dwi; Kasri, Rahmatina Awaliah (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to investigate the relationship between sharia governance and sustainability performance in the Indonesian Islamic banking industry. Sharia governance is measured by the sharia supervisory board (SSB) score and the individual attributes of its members (size, number of meetings, educational background, and diversity). Sustainability performance (SP) is proxied by its economic, environmental, and social dimensions, as defined by the Global Reporting Initiative (GRI) framework. Secondary data from 2010—2020 company reports are used and analyzed using manual content analysis. Panel data regression is also employed to test the hypotheses and identify which individual attributes of the SSB influence sustainability performance. The results show that the SSB has a positive and significant effect on Indonesia’s overall SP of Islamic banking. Among the individual attributes, the frequency of SSB meetings has a positive and significant effect on overall SP, while the diversity of SSB members negatively affects economic and social SP. Meanwhile, SSB member’s size and educational background do not affect overall SP. The findings are expected to enhance understanding of Islamic bank’s development and approaches to addressing sustainability-related issues of Islamic bank. This study also contributes as consideration in the improvement of standard practices or the current implementation of sharia governance in Indonesia and to promote sustainable operations through Islamic corporate governance.